A benchmarking approach for forecasting gas consumption considering subsidy removal. (1st January 2013) - Azadeh, Ali; Saffar, Mohamad Mahdi; Nazari, Tayebeh
This paper presents a benchmark methodology for analysing the effect of cutting off subsidies on the coefficients of related factors in gas consumption pattern prediction. The effects of population (POP), gross domestic production (GDP) and price of energy in the gas consumption are obvious but the coefficients of above factors depend on subsidy. We are therefore able to estimate the required coefficients for obtaining correct results after subsidy elimination. The proposed methodology consists of nine parameters that affect on gas consummation. This study uses data from 19 countries from 1993–2008 as these countries do not have any financial assistance. Moreover, these data are used for predicting gas consumption after subsidies elimination. Several similarity and benchmark parameters are considered and used. The analysis shows some changes in the consumption patterns in the future toward other countries with no subsidies in energy. This is the first study that uses benchmarking approach for gas consumption estimation considering subsidy removal.